Baptism by fire: the pivotal role of ancient conflagrations in evolution of the Earth's flora - He, Tianhua; Lamont, Byron (2018)
Fire became a defining feature of the Earth’s processes as soon as land plants evolved 420 million years ago and has played a major role in shaping the composition and physiognomy of many ecosystems ever since. However, there remains a general lack of appreciation of the place of fire in the origin, evolution, ecology and conservation of the Earth’s biodiversity.We review the literature on the presence of fire throughout the Earth’s history following the evolution of land plants and examine the evidence for the origin and evolution of adaptive functional traits, biomes and major plant groups in relation to fire.We show that: (1) fire activities have fluctuated throughout geological time due to variations in climate, and more importantly in atmospheric oxygen, as these affected fuel levels and flammability; (2) fire promoted the early evolution and spread of major terrestrial plant groups; (3) fire has shaped the floristics, structure and function of major global biomes; and (4) fire has initiated and maintained the evolution of a wide array of fire-adapted functional traits since the evolution of land plants.We conclude that fire has been a fundamental agent of natural selection on terrestrial plants throughout the history of life on the Earth’s land surface. We suggest that a paradigm shift is required to reassess ecological and evolutionary theories that exclude a role for fire, and also there is a need to review fire-suppression policies on ecosystem management and biodiversity conservation in global fire-prone regions.